Proceedings of the 2004 ACM SIGGRAPH International Conference on Virtual Reality Continuum and Its Applications in Industry - V 2004
DOI: 10.1145/1044588.1044670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of network delay on a collaborative motor task with telehaptic and televisual feedback

Abstract: The incorporation of haptic interfaces into collaborative virtual environments is challenging when the users are geographically distributed. Reduction of latency is essential for maintaining realism, causality and the sense of co-presence in collaborative virtual environments during closely-coupled haptic tasks. In this study we consider the effects of varying amounts of simulated constant delay on the performance of a simple collaborative haptic task. The task was performed with haptic feedback alone or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…The authors concluded that participants adopt a move-and-wait strategy to synchronize their movements, consequently increasing the total time required to complete the task. This study, as well as other similar research [3] converge on the conclusion that, in addition to increased time-to-completion, task accuracy also suffers in setups with larger latencies. Furthermore, latency can result in oscillopsia, which is the perception that the visual world appears to swim about or oscillate in space [2].…”
Section: Motivationsupporting
confidence: 84%
See 1 more Smart Citation
“…The authors concluded that participants adopt a move-and-wait strategy to synchronize their movements, consequently increasing the total time required to complete the task. This study, as well as other similar research [3] converge on the conclusion that, in addition to increased time-to-completion, task accuracy also suffers in setups with larger latencies. Furthermore, latency can result in oscillopsia, which is the perception that the visual world appears to swim about or oscillate in space [2].…”
Section: Motivationsupporting
confidence: 84%
“…While end-to-end delay has been clearly identified as a major impairment to DIVEs, jitter has recently been acknowledged as having an even greater impact [10,20,3]. Park and Kenyon [20] conclude that network latency jitter disarms compensatory prediction techniques otherwise available for known constant delay systems.…”
Section: Motivationmentioning
confidence: 99%
“…There have been several attempts to study how the network conditions affect user interaction and cause instability in collaborative scenarios [10,11,12,13]. It is worth mentioning that most of the studies have been focused on only network delays, because they are the main cause of instability.…”
Section: Related Workmentioning
confidence: 99%
“…In a later research, the effects of varying simulated delay on a cooperative task has been studied and evaluated in [10]. During this experiment, the same time-delay compensator was used.…”
Section: Related Workmentioning
confidence: 99%
“…Some researchers have studied the effects of delay or jitter on task performance and their acceptable performance limits [37,38]. The issue of "network-based force feedback" is addressed in [39].…”
Section: Challenges and Related Researchmentioning
confidence: 99%